2004
DOI: 10.1074/jbc.m408477200
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleus-encoded Protein MOC1 Is Essential for Mitochondrial Light Acclimation in Chlamydomonas reinhardtii

Abstract: Mitochondrial respiration plays an important role in optimizing photosynthetic efficiency in plants. As yet, the mechanisms by which plant mitochondria sense and respond to changes in the environment are unclear, particularly when exposed to light. Here we describe the characterization of the Chlamydomonas reinhardtii mutant stm6, which was identified on the basis of impaired state transitions, a mechanism that regulates light harvesting in the chloroplast. The gene disrupted in stm6, termed Moc1, encodes a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 66 publications
9
107
0
1
Order By: Relevance
“…Chlamydomonas reinhardtii wildtype wt13 [23] derived from the original Ebersold/Levine line 137c (CC-125 mt+) [24,25] was used as a model organism. For maintenance and preculturing the algae was continuously grown mixotrophic in liquid cultures of TAP media (Tris Acetate Phosphate) [26] under low light intensities (50 µE m -2 ·s -1 ).…”
Section: Strains and Mediummentioning
confidence: 99%
“…Chlamydomonas reinhardtii wildtype wt13 [23] derived from the original Ebersold/Levine line 137c (CC-125 mt+) [24,25] was used as a model organism. For maintenance and preculturing the algae was continuously grown mixotrophic in liquid cultures of TAP media (Tris Acetate Phosphate) [26] under low light intensities (50 µE m -2 ·s -1 ).…”
Section: Strains and Mediummentioning
confidence: 99%
“…At last, the availability of mutants affected to various extents in their ability to couple ATP synthesis to NADH oxidation is also a useful tool to study the relationship between the mitochondrial energetic status of the cell, hydrogen production, carbon metabolism, and ATP/NADPH adjustment for photosynthesis [62,[64][65][66][67] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 16 [17], (c) [68], (d) [69], (e) [70], (f) [71], (g) [72], (h) [73], (i) [74], (j) [75], (k) [76], (l) [77], (m) [22], (n) [29], (o) [78], (p) [58], (q) [79], (r)[34] …”
Section: Resultsmentioning
confidence: 99%
“…This mutant named stm6 was obtained by random insertional mutagenesis and is affected in the nuclear MOC1 gene [62]. The Moc1 protein belongs to the mitochondrial transcription Termination Factor (mTERF) family.…”
Section: Mutants Affected In the Transcription Of The Mitochondrial Gmentioning
confidence: 99%
See 1 more Smart Citation
“…It promotes transcription termination by binding to a 28-base pair region within the tRNA Leu (UUR) gene at the position immediately adjacent and downstream of the 16S rRNA gene (Kruse et al, 1989). Through bioinformatics tools, its paralogues like sea urchin mtDBP, Drosophila DmTTF, Chlamydomonas reinhardtii Moc1, Mus musculus mTERF, Homo sapiens MTERF2 (mterfd3, mTERFL) and MTERF3 (mterfd1) (Chen et al, 2005;Fernandez-Silva et al, 2001;Li et al, 2005;Roberti et al, 2003Roberti et al, , 2006Schonfeld et al, 2004) with similar structure were found, divided into four subfamilies, and then further characterized. The salient feature of proteins in MTERF family is the containing of variable number of "mterf" motifs of about 30 amino acids in length.…”
Section: Introductionmentioning
confidence: 99%